PCAISO-GT: uma metaheurística co-evolutiva paralela de otimização aplicada ao problema de alocação de berços - Oliveira, Carlos Eduardo de Jesus Guimarães (Universidade do Vale do Rio dos Sinos, 2013)
This paper presents an optimization algorithm based on metaheuristic of Artificial Immune Systems, principles of Game Theory, Co-evolution and parallelization. The objective is find the appropriate combination of the concepts of Game Theory, Co-evolution and Parallelization applied to AISO algorithm (Artificial Immune System Optimization) for solving the Berth Allocation Problem (BAP). Thus, the algorithm is formalized from the above mentioned techniques, forming the PCAISO-GT: Parallel Coevolutionary Artificial Immune System Optimization with Game Theory. Initially, experiments aiming to tune the parameters were performed using different versions of the tool developed. Based on the identified best settings, evaluation experiments were carried out by solving a set of instances of the PAB. The results obtained allowed the appointment of co-evolutionary version associated with game theory as the best solution to the problem under study.
Keywords: Computação natural; Sistema imunológico artificial; Otimização combinatória; Computação evolucionária; Co-evolução; Paralelização; Natural computation; Artificial immune system; Combinatorial optimization; Evolutionary computation; Co-evolution; Parallelization; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação